Gradul de adecvare a sistemului public de pensii din România - Abordare multidimensională - Cristina CIURARU-ANDRICA (Revista Transilvană de Ştiinţe Administrative, 2013)
In order to quantify the adequacy degree of the public pension system in Romania, as well as that of the systems from other member states of the European Union, we applied the calculation methodology proposed by Filip Chybalski in the study entitled “Measuring the Multidimensional Adequacy of Pension Systems in European Countries”. Therefore, we started from a series of indicators put forward by the European Commission, which were grouped into three categories corresponding to the three main dimensions used when defining the adequate character of a pension system, namely income indicators, indicators reflecting poverty levels and gender differences (related to income and poverty levels). Employing these indicators, we determined/measured the adequacy degree of a pension system from a multidimensional perspective. The calculations were applied to 26 European countries over a three-year period, namely 2007, 2009 and 2011. Thus, the outcome of our research included a comparison and, implicitly, a classification. The adequacy degree of the public pension system in Romania revealed improved levels in 2011 as compared to 2007, both in general and at the level of each dimension.